KUALITAS PELAYANAN HOUSEKEEPING DEPARTMENT DI MONA PLAZA HOTEL PEKANBARU - Mahezda Lilis; Endang Sutrisna; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research was conducted at the Mona Plaza Hotel Pekanbaru . This study aims to determine the quality of service of employees Housekeeping Department at Mona Plaza Hotel Pekanbaru . This study aims at a) . To determine the response to a given service employees Housekeeping Department at Mona Plaza Hotel Pekanbaru . b ) . To find any efforts by the company to improve the quality of care Housekeeping Department at Mona Plaza Hotel Pekanbaru .The samples used in this study was 100 respondetsn ( people ) . This study uses Statiscal Descriptive analysis is a technique that describes in detail the issues, based on the data obtained from the questionnaire , and the data obtained will be analyzed to determine the percentage of respondents .The method used in this research is descriptive qualitative , ie by grouping the data compiled in such a way , then connects with theories relating to the problems faced by the organization so that it can be concluded .Boundary problem in this study , the authors only discuss about Quality Housekeeping Services Department provided to guests and any efforts by the company to improve the quality of care Housekeeping Department at Mona Plaza Hotel Pekanbaru . outside of the authors do not discuss this aspect.Identifications of this research is how the quality of housekeeping services at Mona Plaza Hotel Pekanbaru ? and any efforts by the company in an effort to improve the quality of housekeeping services at Mona Plaza Hotel Pekanbaru .Keywords : Reliability, Responsiveness , Assurance , Empathy and Tangibles .